2022
DOI: 10.12659/ajcr.936022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Upper-Body Flexibility Exercise on Golf Performance of Amateur Female Golfer: A Case Report

Abstract: Patient: Female, 43-year-old Final Diagnosis: Amateur golfer Symptoms: Golf swing Medication:— Clinical Procedure: — Specialty: Public Health • Rehabilitation Objective: Unusual or unexpected effect of treatment Background: We investigated the effects of the upper-body flexibility exercises on the golf performance of a female amateur golfer. Case Report: The participant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Information on each study and intervention can be found in Tables 3 and 4. Sample populations for the studies included female golf teams (40), youth female players (12), Korean LPGA tour members (35,36), amateur female golfers (25), NCAA Division 1 golfers (13), and a single, high handicap golfer (32). The duration of each study varied from a single time point, cross-sectional study (8,12,40) to a 12-week training intervention performed twice per week (36).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Information on each study and intervention can be found in Tables 3 and 4. Sample populations for the studies included female golf teams (40), youth female players (12), Korean LPGA tour members (35,36), amateur female golfers (25), NCAA Division 1 golfers (13), and a single, high handicap golfer (32). The duration of each study varied from a single time point, cross-sectional study (8,12,40) to a 12-week training intervention performed twice per week (36).…”
Section: Resultsmentioning
confidence: 99%
“…Jung et al (32) investigated the effects of upper-body flexibility in a single female amateur golfer on maximum rotation angle of the upper body, X-Factor stretch, CHS, and carry distance. The main critique of this research is that the player involved had a high handicap of 20; therefore, the findings are again, not attributable to lower handicap or elite players.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rotation of the upper torso and pelvis plays a crucial role in generating clubhead speed, which is a key factor in achieving greater distance and accuracy in golf shots. Biomechanical research has revealed that the X-Factor, or rotation between the upper torso and pelvic angles, during the swing, is closely linked to clubhead speed and power [4,5]. Additionally, the angles of the upper torso and pelvic rotation, along with their rotational velocities, influence swing efficiency and accuracy [6,7].…”
Section: Introductionmentioning
confidence: 99%